A 7-YEAR STUDY ON SURVIVAL RATE OF FIXED PARTIAL DENTURE AND POST & CORE DONE BY 5TH YEAR DENTAL STUDENTS OF SCHOOL OF DENTAL SCIENCES, UNIVERSITI SAINS MALAYSIA - KHAIRULANAM KAMRUDDIN; TOY ENG TAT; NOR AIDANIZA ABDUL MUTTLIB; RABIHAH ALAWI; NORMASTUR AABD RAHMAN; NAFIJ BIN JAMAYET (International Journal of Pharma and Bio Sciences, 2015)
The restoration of root-filled teeth remains a major concern in dentistry. When a large amount of the clinical crown has been lost, a post provides a way of secure anchoring to the filling material to the tooth. The post is inserted into the root canal and this enables the core to build up and retained. Post and core systems strengthen the root and serve to improve retention of the final restoration. The purpose of this retrospective study was to evaluate the survival and the success rate of the posts and cores and fixed prosthesis that had been done by 5th year dental students in UniversitI Sains Malaysia Health Campus, since 2004 until 2011.The result of this study showed the survival rate for posts and cores for duration of first year was 94.44%and 94.29% in second year. For fixed prosthesis, the survival rate for duration of 1 year was 97.6% but survival rate of 7 years was dropped to 50.0%. Molar tooth had highest failure rate (45.4%), followed by premolar (27.3%) and anterior tooth (27.3%). From the failure samples, posterior tooth had higher rate for failure (72.7%) compared to anterior tooth. The data obtained from this study will be useful to dental students of Universiti Sains Malaysia to assess their clinical skill of doing fixed prosthodontics rehabilitation.